SHIS: Smart healthcare information system for direction guidelines in Hospital Sultanah Maliha, Pulau Langkawi / Nor Atikah Jula Rahman - Jula Rahman, Nor Atikah (2020)
Geographic Information System provides an excellent means for visualizing and analyzing epidemiological data, revealing trends, dependencies and also inter-relationships. In industry and big organizations facility management has become a managing tool of more and more importance. In times of decreasing profit rates and harder competition every company is forced to develop better strategies for resource and facility management. Smart Healthcare Information System (SHIS) is a comprehensive, integrated information system built for managing the operations in showing the detail information about the positions department, direction and treatment procedure in the Hospital. SHIS as any other integrated system, needs time for developing, require special type of professional skills for development and software production for the system. Hospital Information System helps in improving efficiency, both on the cost and the clinical care perspective. This is achieved by avoiding delays, misunderstanding, guideline and confusions. SHIS also helps in improved healthcare information procedure knowledge with better guideline provided, faster the patient or visitors time to see the directory, higher quality information and more versatility in information display. This project provided a basic understanding of how to work with SketchUp Software in GIS, and explore the interactive map the carry out the best result of this project by Using Adobe Flash Player Professional.